Knowledge, attitudes, and practices towards COVID-19 among blood donors during the COVID-19 outbreak - Singh, Ashutosh; Maurya, Pradeep Kumar; Solanki, Archana; Chandra, Tulika; Sachan, Beena (Indian Journal of Community Health, 2022)
Background: Assessments of the blood donors’ knowledge, attitudes, practices, and perceptions of this infection are essential for controlling the spread of COVID-19. Aim and objectives: This study aimed to evaluate the KAP among blood donors towards COVID 19 pandemic and how to increase the number of blood donations during pandemic. Materials and Methods: This study was conducted among 630 blood donors at the Department of Transfusion Medicine, at a tertiary care center in North India. It was an observational study. Statistical analysis: The data were analyzed using Kruskal-Wallis and Mann-Whitney test. To correlate variables Chi-square test was used. Results: The knowledge score of demographic variables marital status, education & occupation showed a significant association, while its association with age, gender, and religion was insignificant. The entire demographic variables under study showed a significant association with Attitude questionnaire 1. According to univariate analysis, the variables Intercept, Unemployed and Physical Labour showed significant impact on knowledge level with the corresponding effect size 0.10 and 0.022. Conclusions: This study reveals that blood donors have good knowledge with positive attitudes and practices. By improving the knowledge with the help of health education platforms, the number of blood donations will also increase.